Audio-Visual Based Picture Story Media for Elementary School Students - Resky Satriya, Restu; Eni Fariyatul Fahyuni (Universitas Pendidikan Ganesha, 2023)
Religious education is important in shaping students' religious understanding and practice. In this regard, the research aims to develop audio and visual-based Islamic picture story learning media to increase understanding of prayer for elementary school students. This type of research is development research using the ADDIE model. The product validity test subjects were 1 learning material expert, 1 learning media expert, and 1 learning expert. The subjects for the product trial (product practicality test) were 19 grade III elementary school students. The methods used to collect data are observation, questionnaires and tests. The instruments used to collect data were questionnaire sheets and test question sheets. Data analysis techniques use qualitative descriptive analysis, quantitative descriptive analysis and inferential statistics. The research results, namely the results of assessments from learning material experts, learning media experts, and learning experts, received a score of 98%, resulting in very good qualifications. The assessment results the students gave received a score of 93.55%, resulting in very good qualifications. The t-test results showed a significant difference in increasing understanding of prayer between the experimental class group and the control class group. It was concluded that Islamic picture story learning media based on audio and visuals effectively increased elementary school students' understanding of prayer.The implication of this research is that the media developed can be used in learning.